2018
DOI: 10.3390/met8030159
|View full text |Cite
|
Sign up to set email alerts
|

Interface Characteristic of Explosive-Welded and Hot-Rolled TA1/X65 Bimetallic Plate

Abstract: TA1/X65 bimetallic plate has a bright future of application by combining the excellent corrosion resistance of TA1 and the high strength of inexpensive X65 steel, while manufacturing large size TA1/X65 bimetallic plate is still a challenging task. Multi-pass hot-rolling is the most common way to achieve a large size bimetallic plate. In this work, interface characteristic of explosive-welded and multi-pass hot-rolled TA1/X65 bimetallic plate is experimentally studied. The microstructure, composition and microh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…As its name suggests, explosives detonation is implemented to provide the impact force for the flyer. It was reported that more than 200 material combinations have been successfully welded by EXW [22], for example, Fe/Ti [23][24][25], Zr/Fe [26], Al/Ti [27], Ti/Ni [28], and Al/Fe [29,30]. For plate welding, two generally used experimental setups are the inclined mode and parallel mode, as shown in Figure 2.…”
Section: Explosive Welding and Gas Gun Weldingmentioning
confidence: 99%
“…As its name suggests, explosives detonation is implemented to provide the impact force for the flyer. It was reported that more than 200 material combinations have been successfully welded by EXW [22], for example, Fe/Ti [23][24][25], Zr/Fe [26], Al/Ti [27], Ti/Ni [28], and Al/Fe [29,30]. For plate welding, two generally used experimental setups are the inclined mode and parallel mode, as shown in Figure 2.…”
Section: Explosive Welding and Gas Gun Weldingmentioning
confidence: 99%
“…LAYERED composites with built-in functionalities are attractive materials for many industrial applications because they offer an optimum balance between manufacturing and service costs, and the durability to perform under their conditions of use. For example, bi-and multi-layer materials composed of reactive metals are used in power, [1] chemical, [2,3] and shipbuilding [4][5][6][7] industries, where corrosive wear of equipment is a significant problem. Many material issues related to the use of hydrogen as a fuel can also be solved by the use of layer composites based on reactive metals.…”
Section: Introductionmentioning
confidence: 99%
“…The research centers involved in analyzing these mechanisms worldwide are: Clad Metal Products USA, the Russian Academy of Science, University in Zagreb Croatia, Sakarya University in Turkey, the University of Tehran in Iran. Very intensive research in this area is in progress in China [3,4]. In Poland, it is studied in centers such as: the Military University of Technology, the Polish Academy of Sciences, UTP University of Science and Technology in Bydgoszcz and Opole University of Technology [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper was to test the structural changes and crack growth after cyclic bending of the steel-titanium clad subjected to heat treatment with various temperature and times of annealing. Investigation of the propagation of fatigue cracks and fatigue life obtained by the method of explosive welding for steel-titanium bimetals is not a common area of focus [19], as research has mainly focused on the bonding process and its parameters [2,3]. However, these studies are particularly relevant due to their high industrial importance.…”
Section: Introductionmentioning
confidence: 99%